Size and site matter: the influence of corpus callosum subregional lesions on the magnitude of cross-education of strength - Morrone, Marco; Martinez, Gianluca; Achene, Antonio; Scaglione, Mariano; Masala, Salvatore; Manca, Andrea; Deriu, Franca (Frontiers in Physiology, 2025)
IntroductionCross-education is an established yet not fully understood phenomenon involving interhemispheric processes within the corpus callosum (CC) that result in strength gains in the untraining limb following training of the contralateral homologous muscles. There is a substantial lack of cross-education studies employing lesional models. This study employed the model of multiple sclerosis, a condition typically featuring demyelinating callosal lesions, to pinpoint CC subregions that mediate cross-education, potentially fostering the mechanistic understanding of the interlimb transfer.MethodsNine individuals with relapsing-remitting multiple sclerosis (median Expanded Disability Status Scale: 3.5) and focal CC lesions underwent a 6-week, high-intensity isokinetic training program (≥80% maximal effort at 10°/s) targeting their stronger ankle dorsiflexors. Sagittal FLAIR MRI scans were segmented into five CC subregions (CC1–CC5), with lesion volumes quantified for each subregion. Strength (peak concentric torque at 10°/s) was measured bilaterally before (PRE) and after (POST) training to determine cross-education, defined as the percentage increase in torque of the untrained, weaker limb. Correlations between lesion volumes in CC subregions and cross-education were analyzed.ResultsBoth the trained (+21.5 ± 15.8%, p = 0.002) and untrained (+35.2 ± 24.9%, p = 0.003) limbs demonstrated post-training strength gains, reducing but not eliminating inter-limb asymmetry. Lesions specifically in the rostral body (CC2) correlated with reduced cross-education magnitude (rs = −0.670, p = 0.048) and smaller improvements in strength asymmetry (rs = 0.809, p = 0.008). No associations were detected in other CC subregions.ConclusionThese findings highlight the pivotal role of specific CC subregions, particularly the rostral body, in mediating cross-education of strength. These findings advance our understanding of CC role in the interhemispheric dynamics underpinning cross-education. Routine MRI can identify patients without CC2 lesions who may benefit from cross-education, providing a practical approach to improving muscle strength when weaker muscles cannot be directly trained.Clinical Trial RegistrationClinicaTrials.Gov, identifier NCT02010398